Diagnosis and treatment of hydrocephalus caused by intracranial Nocardia infection: a case report and review of the literature - Shuang-Qi Gao; Jian-Wei Huang; Ying Guo (Brain Disorders, 2025)
Background: Nocardia infections typically occur in the lungs and skin, with pulmonary involvement being the most common. However, dissemination to other body parts, including the central nervous system (CNS), is not uncommon. Nocardia is generally considered an opportunistic pathogen, primarily affecting immunocompromised individuals. Nevertheless, it can also infect immunocompetent individuals. In this study, we present a case of an immunocompetent patient who developed hydrocephalus due to intracranial Nocardia infection. Case presentation: A 66-year-old male with no signs of immunodeficiency and a healthy immune system underwent surgical resection of a brain mass after presenting with gait instability, headache, and vomiting. Postoperatively, next-generation sequencing (NGS) was performed to confirm Nocardia infection. The patient was treated with a standard antibiotic regimen. Following surgery, the patient's hydrocephalus significantly improved, and no signs of infection or complications were observed during a one-month follow-up period. Conclusions: Intracranial infections induced by Nocardia are rare but can lead to complications such as hydrocephalus if not managed appropriately. Long-term ventricular drainage and appropriate antibiotic therapy are effective treatment strategies for such patients. This case highlights the importance of timely diagnosis and comprehensive management in immunocompetent individuals with Nocardia-related CNS infections.